2019
DOI: 10.3390/jfmk4020031
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Weight Status, Physical activity, Maturation, and Functional Movement in Adolescence: An Overview

Abstract: Obesity, low level of physical activity and dysfunctional movement patterns presents one of the leading health issues that can contribute to increased risk for developing not only metabolic and cardiovascular disease, but also musculoskeletal problems. The aim of this paper is to summarize literature and evidence about relationship between functional movement (FM) patterns, physical activity (PA) level and weight status in average adolescent population. In addition, this paper summarized current evidence about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The final major finding of this systematic review and meta-analysis is the degree to which we found a negative and moderate-to-large association between BMI and FMS™. In the literature, weight status has been shown to consistently impact functional movement performances during childhood and adolescence, with similar evidence found in late athletically determined adolescent populations [ 81 , 82 ]. However, BMI is not without criticism, and, in the context of the data presented in this systematic review and meta-analysis, some caveats may be worth noting.…”
Section: Discussionmentioning
confidence: 76%
“…The final major finding of this systematic review and meta-analysis is the degree to which we found a negative and moderate-to-large association between BMI and FMS™. In the literature, weight status has been shown to consistently impact functional movement performances during childhood and adolescence, with similar evidence found in late athletically determined adolescent populations [ 81 , 82 ]. However, BMI is not without criticism, and, in the context of the data presented in this systematic review and meta-analysis, some caveats may be worth noting.…”
Section: Discussionmentioning
confidence: 76%
“…The lack of strong functional movement capacity may be due to additional factors, such as postural instability, resulting from extended static periods during schooling [20]. As functional movement has been linked with improvements in PA behavior [56,80], these low values are troublesome and indicate it is imperative to focus on growing functional capacities in PE and sporting environments to promote efficient and safe movement among adolescent populations. Functional movement exemplifies the definition of MC, as presented by Robinson et al (2015), in addition to its theorized links with FMS skills [26,81].…”
Section: Discussionmentioning
confidence: 99%
“…Howere no differences were found in females subgroups (i.e., skeletal age, sexual maturation and menarche). This can be explained by the fact that peak biological maturity in female subjects occured about two to three years earlier compared to their male peers [ 18 , 61 , 62 ]. In addition, there were a low number of studies in each analyzed subgroup, it is suggested that by increasing the sample size in the subgroups, the results could have pointed to significant differences.…”
Section: Discussionmentioning
confidence: 99%